OPTIMALISASI PATROLI DIALOGIS SAT SAMAPTA POLRES BREBES GUNA MENCEGAH TINDAK PIDANA CURANMOR DALAM RANGKA TERPELIHARANYA KAMTIBMAS - HAFIZ SATRIA ARIANDA (Police Studies Review, 2022)
The rise of vehicle theft (Curanmor) that is troubling the community causes disruption of public-order and security. Police as protectors of the community are trying to maintain public-order and security through the dialogical patrol. The role of these patrols is very important in preventing vehicle theft. This research aims to describe the vehicle thefts, to describe the role of the Uniform-Police Unit dialogical patrol and to identify the factors that affect the dialogical patrol in preventing vehicle thefts in Brebes City Police. The theories used in this study are SWOT and management theories. Furthermore, the concept used is patrol, dialogical patrol, vehicle theft, Samapta unit, and regulation of head of the maintenance agency. This research was conducted using qualitative approach with field research. Data were collected through interviews, observations, and document studies. The results of the study showed that the cases of vehicle thefts are the most prominent ones in Brebes Police. The role of the dialogical patrols by Uniform-Police Unit in preventing vehicle theft is not optimal yet because deficiencies still exist at every stage. The factors are human resources, patrol targets and involvement in Yustisi Operation. The supporting factor is with the assistance provided by other function. To improve the role of the dialogical patrol of the Uniform-Police Unit, special training is needed for the officer.